Experimental study on solution and diffusion process of single carbon dioxide bubble in seawater - Qiusheng LIU (The Japan Society of Mechanical Engineers, 2016)
Solution and diffusion process of carbon dioxide (CO2) in seawater is important in the research and development of CO2 ocean sequestration technology to mitigate global warming. In this study, solution and diffusion process of single CO2 bubble in seawater and pure water were experimentally studied under various pressures and temperatures to evaluate the transport process of CO2 in seawater. The solution process was conducted in a test vessel. CO2 bubble was generated by a CO2 bubble generator installed at the bottom of the vessel. The diameter of CO2 bubble was recorded using a high speed video camera. The pressure and temperature of liquids were measured by using a pressure transducer and thermocouples. Experimental conditions for the temperature ranged from 277 K to 297 K, and the pressure ranged from around 101 kPa up to 400 kPa. It was obtained that the complete solution time decreases with the increase in pressure due to its higher solubility at a higher pressure. It decreases with an increase in temperature arising from a higher diffusivity at a high temperature. It was clarified that the complete solution time for CO2 in seawater is longer than that in pure water due to its relatively lower solubility compared with pure water.